Crystal structure of a putative short‐chain dehydrogenase/reductase from Paraburkholderia xenovorans. Issue 1 (17th December 2021) - Davidson, Jaysón; Nicholas, Kyndall; Young, Jeremy; Conrady, Deborah G.; Mayclin, Stephen; Subramanian, Sandhya; Staker, Bart L.; Myler, Peter J.; Asojo, Oluwatoyin A.
Abstract : The high‐resolution structure of a putative short‐chain reductase from the commercially important bacterium Paraburkholderia xenovorans is reported. P. xenovorans degrades organic wastes such as polychlorinated biphenyls. Abstract : Paraburkholderia xenovorans degrades organic wastes, including polychlorinated biphenyls. The atomic structure of a putative dehydrogenase/reductase (SDR) from P. xenovorans ( Px SDR) was determined in space group P 21 at a resolution of 1.45 Å. Px SDR shares less than 37% sequence identity with any known structure and assembles as a prototypical SDR tetramer. As expected, there is some conformational flexibility and difference in the substrate‐binding cavity, which explains the substrate specificity. Uniquely, the cofactor‐binding cavity of Px SDR is not well conserved and differs from those of other SDRs. Px SDR has an additional seven amino acids that form an additional unique loop within the cofactor‐binding cavity. Further studies are required to determine how these differences affect the enzymatic functions of the SDR.